Characterizing the pathotype of neonatal meningitis causing Escherichia coli (NMEC). Issue 1 (December 2015) - Wijetunge, D.; Gongati, S.; DebRoy, C.; Kim, K.; Couraud, P. O.; Romero, I.; Weksler, B.; Kariyawasam, S.
Abstract Background Neonatal meningitis-causingEscherichia coli (NMEC) is the predominant Gram-negative bacterial pathogen associated with meningitis in newborn infants. High levels of heterogeneity and diversity have been observed in the repertoire of virulence traits and other characteristics among strains of NMEC making it difficult to define the NMEC pathotype. The objective of the present study was to identify genotypic and phenotypic characteristics of NMEC that can be used to distinguish them from commensal E. coli. Methods A total of 53 isolates of NMEC obtained from neonates with meningitis and 48 isolates of fecalE. coli obtained from healthy individuals (HFEC) were comparatively evaluated using five phenotypic (serotyping, serum bactericidal assay, biofilm assay, antimicorbial susceptibility testing, and in vitro cell invasion assay) and three genotypic (phylogrouping, virulence genotyping, and pulsed-field gel electrophoresis) methods. Results A majority (67.92 %) of NMEC belonged to B2 phylogenetic group whereas 59 % of HFEC belonged to groups A and D. Serotyping revealed that the most common O and H types present in NMEC tested were O1 (15 %), O8 (11.3 %), O18 (13.2 %), and H7 (25.3 %). In contrast, none of the HFEC tested belonged to O1 or O18 serogroups. The most common serogroup identified in HFEC was O8 (6.25 %). The virulence genotyping reflected that more than 70 % of NMEC carriedkpsII, K1, neuC, iucC, sitA, andvat genes with only less than 27 % of HFEC possessing these genes. All NMEC and 79 % of HFEC tested were able to invade human cerebral microvascular endothelial cells. No statistically significant difference was observed in the serum resistance phenotype between NMEC and HFEC. The NMEC strains demonstrated a greater ability to form biofilms in Luria Bertani broth medium than did HFEC (79.2 % vs 39.9 %). Conclusion The results of our study demonstrated that virulence genotyping and phylogrouping may assist in defining the potential NMEC pathotype.